The role of indoleamine 2,3-dioxygenase in modulating allergic responses - Salazar, F. (2016)
Dendritic cells (DCs) are key players in the induction and re-elicitation of T helper (Th) 2 immune responses to allergens. Recent data by our group have shown that different C-type lectin receptors (CLRs) on DCs play a major role in allergen recognition and uptake. Particularly, mannose receptor (MR), through modulation of Toll-like receptor (TLR) 4 signalling pathway, can regulate indoleamine 2,3 dioxygenase (IDO) activity favouring Th2 responses. IDO is the rate limiting enzyme involved in tryptophan (TRP) catabolism and it is well known for its role in modulating immune responses through TRP depletion and generation of immune-regulatory metabolites known as kynurenines (KYN). Interestingly, another CLR named dendritic cell-specific intracellular adhesion molecule 3-grabbing non-integrin (DC-SIGN) has been suggested to support Th1 responses; however, the mechanisms involved are unknown. Therefore, the main objective of this project was to evaluate the role of CLRs, with focus on MR and DC-SIGN, and TLRs in modulating the IDO pathway in order to understand their involvement in regulating Th2 immune responses. In addition, it was aimed to study how regulation of IDO levels could impact immune responses in order to understand the signalling pathways involved in this process. The data show that mannosylated allergens can down-regulate TLR4-induced IDO1 and IDO2 expressions as well as IDO activity in human DCs, most likely through binding to the MR. This correlates with data showing increased IDO activity in MRlow-DCs (generated by gene silencing) stimulated with mannan compared with control-DCs (CT-DCs). Conversely, DC-SIGN could exert a differential regulation on IDO levels depending on the antigen’s sugar moieties. Mannosylated ligands could up-regulate TLR4-induced IDO activity through DC-SIGN as evidence by a significant reduction in IDO activity in DC-SIGNlow-DCs upon stimulation with mannan compared with CT-DCs. In contrast, DC-SIGN-specific fucosylated ligands, such as Lewis-X (LeX), can down-regulate IDO activity in a TLR4-dependent manner. It was also found that allergens from diverse source can down-regulate IL-12p70 production by DC, which can further impact T helper cell polarization by reducing IFN-γ production by T cells in autologous co-cultures. Moreover, mannan was also shown to decrease CD86 expression in human DCs, which might impact the IDO pathway, as CD86 is one of the B7 family molecules involved in IDO induction. Furthermore, it was found that the LeX can potentially down-regulate IL-6 production by DCs. In addition, DCs stimulated with LeX and LPS induce lower levels of IFN-γ production by autologous T cells than DCs stimulated with LPS only. This effect was reversed in the presence of KYN, showing that the IDO pathway can regulates T helper cell polarization. TLR4 signalling and LPS exposure have been shown to play a pivotal role in Th2-mediated inflammation and asthma. In addition, it is known that CLRs can modulate TLR-induced responses in an allergy context. Therefore, we further study the role of the TLR signalling pathway in modulating IDO levels in human DCs. TLR4 engagement on human DCs was shown to induce high levels of both IDO isoforms. DCs primed with LPS induce much higher levels of IDO than single LPS controls, inducing a cellular re-programing. This was characterized by an induction of anti-inflammatory mediators such as IL-10 and the transcription factor aryl-hydrocarbon receptor (AhR); the last has been previously linked with the IDO pathway in mouse DCs. Intriguingly, TLR9 engagement with synthetic cytosine-phosphate guanosine (CpG) A motifs was able to down-regulate IDO and induce a pro-inflammatory phenotype in human DCs. Future studies should aim at evaluating their implications in immune responses under tolerance and during infection. Finally, the study was aimed at elucidating the intracellular molecules involved in IDO regulation in human DCs. The analysis was first focused on AhR, a ligand-dependent transcription factor that have been suggested to modulate IDO levels in mouse DCs. It was shown for the first time that TLR4 induction of IDO was dependent on AhR in human DCs. In addition, AhR gene expression as well as AhR activity were reduced in DCs stimulated with mannan and LPS compared with LPS only controls. This data suggest that MR can regulate IDO levels by interfering with AhR expression. Furthermore, it was shown that the NF-κB pathway is key in regulating IDO levels through CLRs and TLRs in human DCs. Particularly, RelB, a member of the non-canonical pathway, expression correlates with the levels of AhR, suggesting that a functional and/or physical association between them might be involved in regulating IDO levels in human DCs. Future studies should aim at elucidating such interactions. To sum up, this project has shown the pivotal role of CLRs and TLRs in modulating the IDO pathway in human DCs, which can affect DC phenotype and function and impact immune responses. In addition, we have gained some understanding into the molecular mechanisms of IDO modulation which might involve cooperation between different transcription factors such as AhR and RelB. These data give new insights into how glycosylated allergens can induce Th2 immune responses, which can pave the way to develop better therapeutic strategies to fight back allergy related diseases.